Pengaruh Remunerasi dan Motivasi Pegawai terhadap Kinerja di Puskesmas Pasundan dan Puskesmas Talaga Bodas Kota Bandung - Bellany Apriono Roykardo; Nina Nurani (Syntax Corporation Indonesia, 2024)
Employee performance, especially in health services in the Health Insurance Era, is a very important concern today. This study aims to determine the partial and simultaneous effect of employee remuneration and motivation on employee performance at Pasundan Health Center and Talaga Bodas Health Center Bandung City. This study used verificative descriptive research through survei and questionnaire methods as data collection instruments. The sample of this study is probability sampling consisting of 63 respondents or the total number of employees at Pasundan Health Center and Talaga Bodas Health Center Bandung City. Data analysis was performed using simple and multiple regression techniques to assess the influence of the independent variabel on the dependent variabel. The results showed that partially and simultaneously employee remuneration and motivation had a significant influence on improving employee performance at Pasundan Health Center and Talaga Bodas Health Center Bandung City.